KEBIJAKAN TRANSMIGRASI DALAM KERANGKA OTONOMI KHUSUS DI PAPUA: MASALAH DAN HARAPAN - Umi Yuminarti (Research Centre for Population, Indonesian Institute of Sciences, 2017)
Transmigration in Papua is perceived as an important approach to improve welfare, to achieve equity in regional development, and to bond the nation. However, this policy has also been a subject of criticism. Thus, the implementation of transmigration policy in Papua needs to be adjusted along with the enforcement of Special Autonomy Law in this province. The transmigration program is expected to be pro-indigenous (affirmative action). This article discusses the role of transmigration in the development of Papua with some related issues which potentially threaten the existence of the local community. Data and information sources in this study are the result of desk reviews from research reports, articles, books, and supporting documents. The result shows transmigration has a significant role in the development process of Papua. Still, it should consider the fundamental rights of the indigenous to avoid conflict in the community. Besides that, the implementation of transmigration program should follow democratic principles to foster the participation of communities in the development process.Â